2016
DOI: 10.7554/elife.19103
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive excitatory input map of the striatum reveals novel functional organization

Abstract: The striatum integrates excitatory inputs from the cortex and the thalamus to control diverse functions. Although the striatum is thought to consist of sensorimotor, associative and limbic domains, their precise demarcations and whether additional functional subdivisions exist remain unclear. How striatal inputs are differentially segregated into each domain is also poorly understood. This study presents a comprehensive map of the excitatory inputs to the mouse striatum. The input patterns reveal boundaries be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

49
503
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 427 publications
(553 citation statements)
references
References 68 publications
49
503
1
Order By: Relevance
“…Although it has long been known that both the mPFC and BLA project to the DMS (Corbit et al, 2013; Hunnicutt et al, 2016; Kelley et al, 1982; McDonald, 1991; Oh et al, 2014; Pan et al, 2010; Wall et al, 2013), we demonstrated for the first time that both inputs overlapped in some DMS areas and targeted the same neuronal population. Previous studies used a single tracer to examine either the mPFC or BLA input; in this study, we employed two viruses encoding different fluorescence proteins (i.e., GFP and tdTomato) to label mPFC and BLA afferents in the same section.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Although it has long been known that both the mPFC and BLA project to the DMS (Corbit et al, 2013; Hunnicutt et al, 2016; Kelley et al, 1982; McDonald, 1991; Oh et al, 2014; Pan et al, 2010; Wall et al, 2013), we demonstrated for the first time that both inputs overlapped in some DMS areas and targeted the same neuronal population. Previous studies used a single tracer to examine either the mPFC or BLA input; in this study, we employed two viruses encoding different fluorescence proteins (i.e., GFP and tdTomato) to label mPFC and BLA afferents in the same section.…”
Section: Discussionmentioning
confidence: 57%
“…To achieve this goal, we first examined whether the Chronos-mediated mPFC input was selectively activated by 405-nm light and the Chrimson-mediated BLA input by 590-nm light. Accumulating evidence suggests that the mPFC projects mainly to the anterior to middle region of the DMS and the BLA innervates the middle-posterior region (Corbit et al, 2013; Hunnicutt et al, 2016; Kelley et al, 1982; McDonald, 1991; Oh et al, 2014; Pan et al, 2010; Wall et al, 2013). We recorded neurons in an anterior DMS area that contained predominantly Chronos-GFP-containing fibers (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Electrophysiological studies have used oblique horizontal slices to activate each pathway separately. However, reports employing this technique have yielded contradictory results, possibly due to species and procedural differences (Smeal et al, 2006; Ding et al, 2008; Smeal et al, 2008) or to the lack of sub-regional specificity (Hunnicutt et al, 2016). With the advent of optogenetics these challenges have been largely overcome (Ellender et al, 2011; Sciamanna et al, 2015; Kolodziejczyk and Raymond, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This functional hypothesis is also supported by the fact that the striatum receives topographically organized cortical projections (Hunnicutt et al . ) and shows territory‐specific molecular reactivity (Gangarossa et al . ).…”
Section: Discussionmentioning
confidence: 99%